Management of inflammatory bowel disease associated colonic dysplasia: factors predictive of patient choice and satisfaction. (19th December 2020) - Kabir, Misha; Thomas‐Gibson, Siwan; Hart, Ailsa L.; Tozer, Phil J.; Faiz, Omar; Warusavitarne, Janindra; Wilson, Ana
Abstract: Aim: In cases of prognostic uncertainty and equipoise as to the best management (prophylactic colectomy vs. surveillance) for dysplasia in inflammatory bowel disease (IBD), individualized discussion with the patient is required. Further understanding of patients' preferences is needed. Methods: A nationwide cross‐sectional survey was distributed to adult IBD patients who had never been diagnosed with dysplasia (dysplasia‐naïve) and those who had (dysplasia‐experienced). Risk perceptions and factors that influence management choices were explored. Results: There were 123 respondents. A substantial proportion (29%) of the dysplasia‐experienced respondents did not feel well informed about the associated cancer risk and/or its management by their clinical team. Contributing themes included contradictory advice and lack of personalized information regarding their cancer risk, alternative management options and impact on long‐term quality of life. Decisional regret and health‐related quality of life amongst those who chose either surveillance or surgery were comparable, but cancer‐related worry scores were elevated in the surveillance group. The dysplasia‐naïve respondents reported that they would only consider having a prophylactic colectomy if they had on average a 50% or even higher risk of developing cancer. On multivariable logistic regression analyses, predictors of colectomy or surveillance preference included ethnicity, personality traits such as health locus of control (whether health status is influenced by luck) and differences in perception of what a low risk of cancer is. Conclusions: This study identifies predictive factors that can influence decision‐making and satisfaction with the counselling process when IBD dysplasia is diagnosed. Further qualitative exploration of cultural themes would be informative.